11.4: The Fabrication of Flexible Electrofluidic Display Arrays Based on PEN Substrate. (28th November 2018) - Li, Hui; Zhao, Weiwei; Jiang, Hongwei; Yue, Qiao; Tang, Biao; Dou, Yingying; Shui, Lingling; Zhou, Guofu
Abstract : Flexible electrofluidic display (FLEFD), as one of the most promising reflective display technology, has drawn an increasing attention in recent years. In this study, we report the fabrication process for the FLEFD based on the flexible PEN film with ITO layer on the surface. The hyflon material was selected as the hydrophobic insulator layer to control the fabrication temperature below 170°C, and the photoresist was used to manufacture the pixel grids. After oil filing and packaging process, the electrical properties and optical properties of FLEFD were both taken into consideration. The results showed that FLEFD presented good display characteristics. The driving voltage of flexible device was 14V when the bending radius of curvature was 10cm. Furthermore, response time for the device was 18ms, and the aperture opening ratio was 42.5%.